Kaji Pengaruh Anti-Roll Bar pada Suspensi Independen Depan Kendaraan ATV Z200 Terhadap Perilaku Body Roll - Teguh Budi S Abunaim (Jurnal Rekayasa Mesin, 2009)
In order to operated at field which vary, ATV ( All Terrain Vehicle) designed to have ability to maneuver which is supported with strong and light frame construction, taft machine and also adequate suspension system. Almost similar to car, ATV have applied suspension independent. The target of this research is to know anti-roll bar appliance installation influence at front suspension system of ATV Z200 to behavioral reduction of roll body, when vehicle in a condition curve (cornering). Analysis roll body conducted by using transfer analysis method with visual MSC software of Nastran 2004Result of this analysis will give reduction graph of roll body angle to speed of vehicle (10,20 and 30 km/hour) as function of displacement vertical from appliance lever arm anti bar roll. This angle is measured from vertical line with straightening of road to a line through a center of mass (center of gravity or shortened, CG) w. Which is vertical with frame. Result of this research showing that by equipment of anti bar roll, behavioral of roll from body vehicle of ATV Z200 when curve can decrease, that is equal to 17,925 % for the speed of 10 km/hour, 13,924 % for the speed of 20 km/hour, and 9,485 % for the speed of 30 km/hour.